Rapunzel (Young Reading Level 1) - Guicciardini,Desideria (UK Usborne Export, 2010)
In "Rapunzel" (Young Reading Level 1), Rapunzel, a girl with exceptionally long hair, is imprisoned in a tower by an evil witch. The witch keeps Rapunzel from leaving, making her feel lonely and miserable. One day, a prince hears Rapunzel singing and falls in love with her. He visits her by letting down her hair, and they decide to escape. However, the witch finds out and cuts Rapunzel's hair, casting spells on both Rapunzel and the prince, leading to their separation and misfortunes. Eventually, Rapunzel's tears restore the prince's sight, and they are reunited, ending the story happily ever after.